2016
DOI: 10.1177/0306624x15588773
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relation Between General Well-Being and Self-Esteem

Abstract: This study investigated the longitudinal relation between general well-being and self-esteem of male adolescents with severe psychiatric disorders. Moreover, the transition out of secure residential care was studied. Adolescents ( N = 172) were assessed three times with 6 months between each assessment. The sample comprised adolescents who were admitted throughout the entire study ( n = 116) and who had been discharged at 6/12 months follow-up ( n = 56). General well-being and self-esteem were stable concepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
10
0
2
Order By: Relevance
“…Twenty articles reported on forensic samples, 20 on prisoner samples, and one article was a randomized controlled trial (RCT) assigning mentally ill offenders to either forensic treatment or prison (Cosden, Ellens, Schnell, & Yamini-Diouf, 2005). Five articles reported on youth (Barendregt, Van Der Laan, Bongers, & Van Nieuwenhuizen, 2016, 2018; Van Damme, Colins, De Maeyer, Vermeiren, & Vanderplasschen, 2015; Van Damme, Hoeve, et al, 2015; Van Damme, Hoeve, Vermeiren, Vanderplasschen, & Colins, 2016) and two reported on elderly samples (Combalbert et al, 2017; De Smet et al, 2017). Three articles reported on offenders with substance use disorders (Broner, Lattimore, Cowell, & Schlenger, 2004; Metz et al, 2010; Prendergast, McCollister, & Warda, 2017), while among the 21 prisoner articles, two reported on offenders with mental health problems other than substance use disorders (Jacoby & Kozie-Peak, 1997; Zwemstra, Masthoff, Trompenaars, & De Vries, 2009) and two excluded based on this (Carcedo, Perlman, Lopez, & Orgaz, 2012; Carcedo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty articles reported on forensic samples, 20 on prisoner samples, and one article was a randomized controlled trial (RCT) assigning mentally ill offenders to either forensic treatment or prison (Cosden, Ellens, Schnell, & Yamini-Diouf, 2005). Five articles reported on youth (Barendregt, Van Der Laan, Bongers, & Van Nieuwenhuizen, 2016, 2018; Van Damme, Colins, De Maeyer, Vermeiren, & Vanderplasschen, 2015; Van Damme, Hoeve, et al, 2015; Van Damme, Hoeve, Vermeiren, Vanderplasschen, & Colins, 2016) and two reported on elderly samples (Combalbert et al, 2017; De Smet et al, 2017). Three articles reported on offenders with substance use disorders (Broner, Lattimore, Cowell, & Schlenger, 2004; Metz et al, 2010; Prendergast, McCollister, & Warda, 2017), while among the 21 prisoner articles, two reported on offenders with mental health problems other than substance use disorders (Jacoby & Kozie-Peak, 1997; Zwemstra, Masthoff, Trompenaars, & De Vries, 2009) and two excluded based on this (Carcedo, Perlman, Lopez, & Orgaz, 2012; Carcedo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Relationships with staff included agreement with items such as “I trust the staff here” and “Staff is generally concerned with my welfare.” Social relationships QoL was related to readiness to change both 1 and 2 months later; the readiness to change dimension was measured through items such as “Maybe this place will be able to help me” and “I guess I have faults, but there’s nothing I really need to change.” Van Damme, Colins, and colleagues (2015) also reported that exposure to trauma and low socioeconomic status were related to poorer QoL in all four domains in a youth sample. In Barendregt et al’s (2016) longitudinal study of youth forensic patients, QoL and self-esteem were correlated over three points in time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been underlined to include the young person's subjective perspectives of the living conditions when assessing his/her wellbeing while being in care (for instance, Barendregt et al 2015;Bradshaw et al 2013;Clery et al 2014;Main and Bradshaw 2012). The use of subjective perspectives as (part of) a monitoring system enables young people having a say in articulating those elements that matter to their own well-being (UNICEF Office of Research 2013).…”
Section: Residential Care Living Environmentmentioning
confidence: 99%